Critical Discourse Analysis as Queer Linguistics: Religious pro- and anti-LGBT equality framing and counterframing in two letters to the editor in the City Press - Mongie, Lauren (Stellenbosch Papers in Linguistics Plus, 2016)
This article is situated at the intersection of the applied linguistic fields of Critical Discourse Analysis (CDA), Collective Action Framing (CAF) and a sociolinguistic field recently referred to as “queer linguistics” (QL). Drawing on a qualitative method of analysis, the article investigates the discursive (re)production of religiously-motivated arguments in favour of and against LGBT equality in two letters to the editor in the City Press newspaper. The paper aims to illustrate the ways in which religiously-framed pro- and anti-LGBT-equality arguments are discursively constructed in public discourses, and to demonstrate the methodological overlap between CDA and QL, and between CDA and CAF. The article’s findings reveal that both the pro- and anti-LGBT-equality letters frame their religious arguments in ways that echo that which is predicted in the literature by making strategic use of lexical items, modifiers, implicature, presupposition, rhetorical devices, and attributive strategies; and that these discursive devices enable the realisation of the core framing tasks that are necessary for social mobilisation to varying extents. Further, the findings indicate that the anti-LGBT-equality letter is more explicit in its ideological positioning and framing tasks, and that it draws significantly more on disclaimers than the pro-LGBT-equality letter. Lastly, the discourse that is present in the diagnostic, prognostic and motivational framing tasks of the pro-LGBT-equality letter attempts to reframe and counterframe anti-LGBT-equality arguments by providing an alternative perspective of same-sex attraction within the religion frame.